1981
DOI: 10.1111/j.1469-8749.1981.tb08446.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Prognosis after Infantile Spasms: a Statistical Study of Prognostic Factors in 200 Cases

Abstract: SUMMARY A follow‐up study was made on 200 children (115 boys, 85 girls) who had had infantile spasms, in order to compare their present condition over the age of six years with various prognostic factors. 48 of the children (30 males and 18 females) had died, and all the rest were aged six years or older at the time of final follow‐up. 139 of the children had received ACTH therapy: at final follow‐up, spasms had ceased in 43.5 per cent, and about the same proportion showed normal physical development; 23 per c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
4
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(45 citation statements)
references
References 11 publications
(3 reference statements)
3
37
4
1
Order By: Relevance
“…Among patients with IS and epilepsy with ES, a patient with a localized PET lesion or a combination of PET and MRI lesions was shown to be the most ideal candidate for resective surgery [13,15,18,24,25]. However, the natural course of patients with these epilepsies who had not responded to medical treatment was not sufficiently investigated before considering [5,7]. Kramer et al [10] identified 22 (33%) of 67 cases of patients with WS and more than two focal features, which was similar to our result (23/69 cases).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Among patients with IS and epilepsy with ES, a patient with a localized PET lesion or a combination of PET and MRI lesions was shown to be the most ideal candidate for resective surgery [13,15,18,24,25]. However, the natural course of patients with these epilepsies who had not responded to medical treatment was not sufficiently investigated before considering [5,7]. Kramer et al [10] identified 22 (33%) of 67 cases of patients with WS and more than two focal features, which was similar to our result (23/69 cases).…”
Section: Discussionmentioning
confidence: 98%
“…Seizures and intellectual prognoses are generally poor. In 20-30% of the patients, IS evolves to Lennox-Gastaut syndrome [4][5][6]. In the other 20-30% of the patients, IS either transforms into focal or multifocal epilepsy although only a few detailed studies on patients whose epilepsy evolved into focal epilepsy following IS have been documented [7][8][9].…”
Section: Introductionmentioning
confidence: 96%
“…In the early 1980s, most studies found identified symptomatic etiologies in approximately 45-60% of patients (18). As seen in our study more recent studies have consistently classified 70-80% of patients into the symptomatic group (8).…”
Section: Discussionmentioning
confidence: 99%
“…10 Several other studies have also commented on the improvement in development with early treatment, 53-55 although some have differentiated this response to occur only in those with cryptogenic infantile spasms. 56 The 2004 American Academy of Neurology/ Child Neurology Society Practice Parameter concluded that the evidence for early treatment was "conflicting" and "insufficient." 33 Despite this, the majority of pediatric epileptologists feel that children with new-onset infantile spasms, regardless of the etiology, should be evaluated, diagnosed, and treated as promptly as possible.…”
Section: Prognosismentioning
confidence: 98%